Assessment of the functional state of left heart in patients with chronic heart failure with preserved ejection fraction - D. V. Vdovenko; R. A. Libis (Российский кардиологический журнал)
Aim. To research the myocardial function in patients with chronic heart failure with preserved left ventricular ejection fraction (CHF-PEF) by speckle tracking echocardiography and function of the left atrium.Material and methods. Eighty patients aged from 50 to 68 years with verified CHF-PEF with NYHA (New York Heart Association) class I-IIa and stage A-C of the ABCD classification of the American College of Cardiology, and 30 healthy persons were examined. CHF-PEF was initiated by arterial hypertension and coronary artery disease. In our study we use 6-minute walk test to evaluate the functional class of CHF-PEF, echocardiography and speckle-tracking echocardiography to examine left ventricle systolic, diastolic function and speckle tracking echocardiography to determine the parameters of the myocardial deformation.Results. Patients were divided as followed: 27% had stage A of CHF, 47,9% — stage B, 25,1% — stage C. The average left ventricular ejection fraction (by Simpson’s method) was 63,3±4,43%. Indexed end systolic volume of the left atrium (LP) in CHF-SFV patients 45,2±8,1 ml/m2. All patients had the diastolic dysfunction: 60 patients had abnormal relaxation pattern, and 20 patients had pseudonormal pattern. Patients with CHF-PEF had reduced global longitudinal strain (GLS) -16,56±2,61% and GLS rate (GLSR) -0,75±0,11s-1 of the left ventricle and reduced segmental strain and strain rate in basal anteroseptal (-14,72±2,54% and -0,76±0,05s-1) and basal anterolateral (-14,27±3,29% and -0,79±0,12s-1) segments. Also patients with CHF-PEF has lower reduction of the circular strain and strain rate (-16,63±3,5% and -1,43±0,21s-1), (p<0,05) in comparison with the GLS. Changes of the radial strain and strain rate were not revealed. Positive correlation between GLS and left atrium volume (r=0,601, р<0,01) was found.Conclusion. In patients with CHF-PEF we revealed abnormal relaxation pattern and pseudonormal pattern of the diastolic dysfunction. Reduced global and segmental strain and strain rate of the left ventricle were shown, circular strain was slightly reduced, radial strain was unchanged.